2006
DOI: 10.1007/s10641-006-9007-6
|View full text |Cite
|
Sign up to set email alerts
|

Residency and movement patterns of bonnethead sharks, Sphyrna tiburo, in a large Florida estuary

Abstract: The use of a coastal estuary by bonnethead sharks, Sphyrna tiburo, was examined by acoustic monitoring, gillnet sampling and tagrecapture studies. Acoustic monitoring data were used to define the residency and movement patterns of sharks within Pine Island Sound, Charlotte Harbor, Florida. Sharks were monitored for periods of 1-173 days with individuals regularly moving in and out of the detection range of the acoustic system. Patterns of movement could not be correlated with tidal level or time of day. Home r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 34 publications
9
95
1
1
Order By: Relevance
“…When spawning, females move into offshore waters of higher salinity when a corresponding pattern of older individuals are observed offshore (Dickinson et al 2006). This movement of prey can potentially drive larger bonnetheads further from the coast, which is reflected in the decrease in 未 13 C and confirmed using observed offshore seasonal movement patterns (Heupel et al 2006, Ubeda et al 2009.…”
supporting
confidence: 73%
“…When spawning, females move into offshore waters of higher salinity when a corresponding pattern of older individuals are observed offshore (Dickinson et al 2006). This movement of prey can potentially drive larger bonnetheads further from the coast, which is reflected in the decrease in 未 13 C and confirmed using observed offshore seasonal movement patterns (Heupel et al 2006, Ubeda et al 2009.…”
supporting
confidence: 73%
“…Changes in salinity offer the most intuitive explanation for the changes in habitat use shown by tagged Bonnetheads, in line with previous findings for this species [4,6,15]. We found that Bonnetheads generally remained at Katrina Cut while the cut was open and made a general westward shift once the cut was closed, as seen from the IDW analysis.…”
Section: Discussionsupporting
confidence: 91%
“…(3) Twenty nocturnal gillnet collections were conducted along the 3 transects at our study site. Gillnet gear specifications (180 脳 3 m, 11.8 cm stretched mesh, weighted) and survey procedures followed those used by Heupel et al (2006) and Wiley & Simpfendorfer (2007). This procedure is highly selective for particular nearshore predators, such as juvenile sharks (Heupel et al 2006, Wiley & Simpfendorfer 2007.…”
Section: Methodsmentioning
confidence: 99%